Adoption of direct-seeded rice (DSR) as a result of labor shortages in the Indo-Gangetic plains due to restrictions on migrant labor - CGIAR Research Program on Rice (2021)
Direct Seeded rice (DSR) is being promoted in countries such as India. Evidence, currently being collated, suggests tha COVID-19 has given a boost to DSR uptake due to labor shortages. This potentially has huge implications for a radical change in land and crop management practices in NW India